Sound Images of the Ocean in Research and Monitoring - Wille, Peter C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Ocean acoustics comprises a key subfield of research, providing indispensable tools for the exploration of the seafloor, other underwater formations and processes. Sound Images of the Ocean employs 400 sound images, contributed by 120 author/marine experts from 22 nations, to create a comprehensive overview of acoustic imaging applications in the sea. This remarkable ensemble spans fields of geophysical research, off-shore industrial and economic activities, national surveillance, and protection of the ocean and continental shelves. Written to be accessible to professionals in diverse related fields, the concise accompanying explanations of the complex relationships revealed by the images strive to condense the results into the essential "message." For readers, this remarkable atlas develops an interdisciplinary understanding of underwater acoustics and its diagnostic capabilities to visualize in detail the two thirds of the surface of the globe otherwise hidden from view.
The Basic Facts of Imaging the Ocean -- Preliminary Remarks -- Alternatives to Imaging the Sea by Sound and First Acoustic Trials -- Acoustic Features of the Sea -- Technical and Physical Characteristics of High Resolution Echosounders -- Applications of Acoustic Imaging the Ocean -- The Sea Floor $1 (BNatural Formations -- The Ocean Volume -- Man-made Matter.s
Keywords: Earth sciences; Geophysics; Oceanography; Geotechnical engineering; Geographical information systems; Acoustics; Environmental sciences; Earth Sciences; Oceanography; Acoustics; Environmental Physics; Geophysics/Geodesy.; Geographical Information Systems/Cartography.; Geotechnical Engineering & Applied Earth Sciences; Electronic books